Erasmus students expectations: a qualitative study in portuguese context - Silva, Susana (2017)
The European Commission presents the Erasmus+ Programme as a tool to achieving economic growth and creating highly-skilled jobs in Europe, in order to strengthen its position as a knowledgebased economy. This programme aims to improve the quality and relevance of higher education, strengthening quality through mobility and cross-border cooperation, making the knowledge triangle work: linking higher education, research and business to achieve excellence and bring about regional development, and therefore improving governance and funding. The aim of this work is to analyse and understand the Erasmus+ student’s expectations that choose a Portuguese higher education institution to perform their Erasmus+ experience. 54 Semi-structured interviews were conducted with Erasmus+ students. The main results showed that the motivations to have an Erasmus+ experience were the need to learn another language and add cultural background to their personal experience. It is also understood as a good way to develop their knowledge in academic and personal learning, and to promote their employability. Erasmus+ students believe that their curriculum vitae is valued, gaining more flexibility and more competence to work in the international environment. Their expectations are to improve the domain of a foreign language, to increase personal and professional independence, to ameliorate academic and communication skills, and to have more responsibility and comprehension about professional environments. The return to the home country is also referred as a relevant moment in this experience. Students expect to be more confident in that occasion, to have more personal and professional skills that facilitate their employability. The reached results allowed obtaining the following evidences: (1) the main motivations of students in an Erasmus+ programme to choose an institution were the good weather conditions, similar culture, language facilities, good networks between the home and host institutions, and personal development.; (2) the personal development includes academic and learning aspects of development of the individual curriculum vitae as well as being a facilitator to their professional integration in the market labour since that companies value international mobility experiences, which shows personal flexibility and a more natural ability to work internationally; (3) in the mobility process is important to have good processual organization of the host institution, the teachers availability to help foreign students and the fact that all the staff in the host institution can speak English; and (4) the soft skills development of students, namely communication, independency, responsibility and confidence, as well as academic skill, which may potentiate students employability at home countries.